Semantics, Algorithmics and Logic: Basic Research in Computer Science. BRICS Inaugural Talk - Winskel, Glynn (BRICS Report Series, 1994)
This is a transcript of a talk at the inauguration of BRICS, Basic Research in Computer Science, Centre of the Danish Research Foundation, on 2 February 1994 at the Steno museum, University of Aarhus, Denmark.